Isolation and Screening of Waterborne Actinomycetes for Their Antistaphylococcal Activity - Hans, Amrit Kaur (My University, 2012)
Due to emergence of multidrug resistance in bacteria and lower efficacy of the present antimicrobial drugs there is an urgent need to explore newer sources and to develop them as potent antimicrobials. Actinomycetes are powerhouse of the bioactive compounds e.g. Streptomyces genus which is known to produce 80% of the known antibiotics. The current study is focused on isolation and screening of actinomycetes from fresh water bodies for anti- staphylococcal activity. Water samples from three different locations (Harike wetland area, Bhakhra canal, Patiala and Allahabad confluence, Allahabad) were collected and subjected for the selective isolation using Kuster’s agar and Starch casein nitrate media. A total of 27 actinomycetes were recovered from water samples from Harike wetland area. No actinomycetes were obtained from other two water samples. All the 27 isolates were purified using streak plate method and maintained on the PDA slants supplemented with 10% glycerol for long term preservation. All the isolates were subjected for production of secondary metabolites on GPB medium. None of the culture filtrate (aqueous fraction) showed any anti-staphylococcal activity. The culture filtrates were then extracted with ethyl acetate. The ethyl acetate fraction was screened for antistaphylococcal activity against three standard Staphylococcus sp. using pre screen assays like KB disc and agar well diffusion. 5 isolates out of 27 exhibited potential antistaphylococcal activity with zone size ranging from 11 to 20.33 mm in KB disc assay and 10.66 to 18.33 mm in agar well diffusion assay. The ethyl acetate fractions of all the 5 isolates were then examined to obtain MIC against test organisms. #11HKSCN showed best activity whereas #2HKSCN shows least activity. The MIC range for all five of the isolates were found to be in between 0.4 to 2.5 mg/ml. Microscopic examination showed that #2HKSCN, #3HKSCN, #6HKSCN, #11HKSCN were Gram positive and #12 HKSCN was Gram negative. Further actinomycetes were biochemically characterized for the production of enzymes like amylase, pectinase and cellulase. Four isolates (#3HKSCN, #6HKSCN, #11HKSCN, #12HKSCN) has the ability to produce amylase enzyme however none of the isolates found to possess the ability to produce pectinase and cellulase enzyme. Further purification of the crude bioactive compounds, structure elucidation and taxonomic identification is warranted to develop these bioactive compounds as pharmacore with potential anti-staphylococcal activity.
Keywords: Actinomycetes; Screening; Anti-staphyloccal Activity